Elements of a Theory of Global Governance (Glocalism: Journal of Culture, Politics and Innovation, 2017)
After the devastation of World War II, a new international community was built, organized under the newly formed United Nations which oversaw the development of a new legal and institutional framework for the maintenance of peace and security. Maintaining global peace and stability served the purpose of limiting violence, but it was also a prerequisite for accelerating “globalisation”. Even during the years of the Cold War, deep tensions between the United States and the Soviet Union facilitated, paradoxically, a deepening of interdependence and coordination among world powers. The logic of MAD (“mutually assured destruction”) determined the awareness of the shared vulnerability of the globe. From the late 1940s to the beginning of the 21st century, a densely complex and interdependent world order emerged. Global interdependence has now progressed to the point where it is beginning to undermine our ability to engage in further cooperation. The need for international cooperation has never been higher and yet effective institutionalized multilateral cooperation has stalled. It is possible to identify four reasons for this blockage, four pathways to gridlock: rising multipolarity, more difficult problems, institutional inertia and institutional fragmentation. Still, there exists a range of instances in which gridlock has not prevented effective global governance from emerging – some “pathways” out of gridlock. The following article discusses the reasons behind gridlock and the four pathways through and beyond it, in order to identify mechanisms through which effective global change can occur. This task, the search for pathways through and beyond gridlock, is a hugely significant one, if global governance is to be once again effective, responsive and fit for purpose.
Keywords: Gridlock; Pathways; Interdependence; Cooperation; Global Governance